Reconstruction Strategies for Mental Health Services in Post-Conflict Middle Eastern Regions: (A Policy Synthesis) - Helsa Nasution; M. Agung Rahmadi; Nazwa Aqela Saragih; Isnaini Fajarwati; Riska Wahyuni Hasibuan; Luthfiah Mawar; Nurzahara Sihombing; Annisa Ardianti Br Tarigan (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
This study presents a comprehensive analysis of reconstruction strategies for mental health services in post-conflict regions of the Middle East, based on a meta-synthesis of 87 policies and intervention programs issued between 2010 and 2023. The findings indicate that 73.4 percent of initiatives did not meet their intended targets due to infrastructural limitations, resulting in a service dropout rate of 62.8 percent. The implementation of the Stepped Care Model shows a 47.2 percent improvement in service access (p = 0.001), while the integration of mental health services into primary health care systems increases overall coverage by 56.3 percent (p = 0.001). Task shifting to community health workers enhances efficiency by 38.9 percent (p = 0.01) with a cost-effectiveness ratio of 1 to 2.7, and community-based programs demonstrate a sustainability rate of 71.2 percent compared to 43.5 percent in conventional approaches. These findings build upon the work of Hamamra et al. (2025) and Werner et al. (2023) on post-conflict mental health interventions and show that hybrid models combining formal and informal structures yield better performance, with an effect size (Cohen's d) of 0.82. The main contribution of this study lies in identifying adaptive implementation patterns that align with resource limitations, socio-cultural dynamics, and systemic reconstruction needs in post-conflict settings.